Peran Guru Pendidikan Agama Kristen Dalam Meningkatkan Minat Belajar Peserta Didik Pada Masa Pandemi Covid 19 Di SD Swasta Alfa Omega Ngabang - Darlina Darlina; Henni Somantik; Sanci Amelia Malelak; Marthen Mau (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Education is an integral part of human life starting from birth until the end of life. Students' interest in learning is an important aspect in the learning process, especially in character formation and understanding learning concepts. Teachers have a crucial role in facilitating students' interest in learning, because they are the main actors in the internalization of character education. However, the COVID-19 pandemic has changed the educational landscape by forcing a transition to distance learning. The impact is felt in the decline in students' interest in learning, which is caused by various factors such as physical health and changing learning environments. This research highlights the decline in students' interest in learning since the start of the pandemic, focusing on changes in learning motivation and behavior.